Identification and optimisation of a 4′, 5-bisthiazole series of selective phosphatidylinositol-3 kinase alpha inhibitors. Issue 17 (1st September 2015) - Fairhurst, Robin A.; Imbach-Weese, Patricia; Gerspacher, Marc; Caravatti, Giorgio; Furet, Pascal; Zoller, Thomas; Fritsch, Christine; Haasen, Dorothea; Trappe, Joerg; Guthy, Daniel A.; Arz, Dorothee; Wirth, Jasmin
Graphical abstract